2020
DOI: 10.15293/2658-6762.2002.08
|View full text |Cite
|
Sign up to set email alerts
|

Use of information and communication technologies (ICT) by university students: Evaluating the effectiveness for learning purposes

Abstract: Проблема и цель. В статье исследована проблема эффективного применения инфокоммуникационных технологий (ИКТ) студентами в образовательном процессе вуза. Цель исследованияоценка целенаправленности применения современных ИКТ студентами в образовательном процессе вуза. Методология. Разработана анкета, содержащая 11 вопросов. Опрошены 150 студентов разных курсов обучения бакалавриата и магистратуры. С применением системного и синергетического подходов выполнены анализ и обобщение ответов опрошенных студентов. Резу… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
(1 reference statement)
0
1
0
Order By: Relevance
“…At the same time, Sanders and George (2017) concluded that the initial perception of the ICT role and capabilities in the educational process was too audacious. In particular, for most students, ICT has not yet become a tool that contributes to the formation of a young creative specialist (Andreev et al 2020;Vasilieva et al 2020). Therefore, ICT implementation in an educational process requires setting achievable goals based on the relevance of the educational contexts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…At the same time, Sanders and George (2017) concluded that the initial perception of the ICT role and capabilities in the educational process was too audacious. In particular, for most students, ICT has not yet become a tool that contributes to the formation of a young creative specialist (Andreev et al 2020;Vasilieva et al 2020). Therefore, ICT implementation in an educational process requires setting achievable goals based on the relevance of the educational contexts.…”
Section: Literature Reviewmentioning
confidence: 99%